Developing a fast photochemical calculator for an integrated assessment model. (28th December 2012) - Reis, Lara Aleluia; Melas, Dimitrios; Peters, Bernhard J.; Zachary, Daniel S.
The use of integrated assessment models, in air quality policy, which combines atmospheric models with others from different fields, raises the need of developing specific air quality modelling concepts. The air quality model, AUSTAL2000-AYLTP uses an adapted version of AUSTAL2000 model to calculate transport coupled with a fast photochemical module. Two approaches are compared: one using a look-up table and the other using a coupled box model. The lookup table has been built using the OZIPR model by simulating a large set of possible combinations of meteorological variables and precursor concentrations. The second approach consists of coupling the Lagrangian model AUSTAL2000 with the OZIPR box model. In both approaches the photochemistry is included in the mode by using a quasi-linear reaction rates coefficient which is used to affect the mass of the Lagrangian particles. We discuss the differences and the suitability of the two model versions, through exploring CPU time flexibility, applicability and accuracy.